PENGARUH AKUNTABILITAS, TEKANAN EKSTERNAL, KOMITMEN MANAJEMEN, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN (Studi pada Satuan Kerja perangkat daerah kabupaten Indragiri Hulu - Farid Hamdi; Hardi Hardi; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Transparency of financial reporting requires organizations to present the financial statements are free from material false information and biased to outsiders. This is consistent with the concept of reliability of the information in the financial statements that should be free of errors and misleading understanding of the material, presenting any facts honestly, and can be verified. .This Study examined the effects of accountability, external pressure, hesitated environment, and commitment to leadership on the transparency of financial reporting. The sample studied consisted of 27 sectors in Indragiri Hulu. the analytical techniques used to test hypotheses is purposive sampling. Data were analyzed using multiple regression analysis using SPSS (Statistical Product and Service Solution) 17 version.The results showed that accountability, external pressure, management commitment, and competence of human resources who do have the effect of transparency of financial reporting. Accountability was significant 0,034 0,033 external pressure was significant. Demonstrated management commitment 0.000 significance. Highlights the competence of human resources 0.000. This decision was made are all variables significant effect on the transparency of financial reporting.Keywords: Accountability, External Pressure, commitment management, human resources, and financial transparency